Design of a force measuring unit for robotic applications - Rónai, László (Design of Machines and Structures, 2024)
The paper deals with design process of a force measuring unit, which is capable to mount onto a robot or to integrate into a measuring device. The main element is a beam type load cell equipped with strain gauges in Wheatstone bridge configuration. In order to measure the force only in one direction a linear guide rail is used to lock the degrees of freedom. The unit will have a microcontroller board to process and transfer the data to a personal computer. Furthermore, the system will be capable to intervene processes thanks to the digital inputs and outputs of the electric board. The paper introduces the 3D model of the device, and its components.